The halo model of origin images: Conceptualisation and initial empirical test. Issue 4 (11th June 2013) - Josiassen, Alexander; Lukas, Bryan A.; Whitwell, Gregory J.; Assaf, A. George
ABSTRACT: National origin has gained importance as a marketing tool for practitioners to sell their goods and services. However, because origin‐image research has been troubled by several fundamental limitations, academia has become sceptical of the current status and strategic implications of the concept. The aim of this paper was threefold, namely, to provide a state‐of‐the‐art review of origin‐image research in marketing, develop and empirically test a new origin‐image model and, present the implications of the study. Copyright © 2013 John Wiley & Sons, Ltd.